Democratic phoenix : - Norris, Pippa (Cambridge University Press, 2002)
Conventional wisdom suggests that citizens in many countries have become disengaged from traditional political participation. Commentators highlight warning signs of sagging electoral turnout, rising anti-party sentiment, and the decay of civic organizations. But are these concerns justified? This book compares systematic evidence in nearly two hundred countries worldwide and suggests reasons for questioning assumptions of decline. Not only is the obituary for older forms of political activism premature, but new forms of modern civic engagement may be emerging.